To solve for a variable means to isolate the variable on one side of the equation.
C = 2ar
Simply divide both side by 2a.
Answer: C/2a = r
Done.
there are 18 oranges in box A and 36 in box B, what is the ratio of box A to box B
Answer:
1 : 2
Step-by-step explanation:
Express the ratio as the number of oranges in each box, that is
box A : box B
= 18 : 36
Simplify the ratio by dividing both parts by 18, thus
ratio = 1 : 2 ← in simplest form
The formula for the circumference of a circle is C = 2πr, where r is the radius. Rearrange the formula to solve for r and select the correct option below.
-9.5 as a mixed number
You know that .5 = 0.5 = 5/10 = 1/2.
Mixed number sought: -9_1/2.
Critique the reasoning of others. Oriana said that the difference between 9.298 and 3.01 was 8.997.
Was she correct? If not, what error did she make?
Answer: Oriana was not correct, because she didn't line up the decimal points of the numbers [tex]9.298[/tex] and [tex]3.01[/tex]
Step-by-step explanation:
By definition, the "Difference" is the result of a subtraction.
In order to subtract the decimal numbers [tex]9.298[/tex] and [tex]3.01.[/tex], Oriana needed to apply these steps:
1. Write one number under the other. The decimal points must be lined up:
[tex]9.298 \\3.01-\\..........[/tex]
2. Since the decimal numbers must have the same number of decimal places, she needed to add zeros to the right side:
[tex]9.298 \\3.010-\\..........[/tex]
3. Subtract the numbers and put the decimal point in the result:
[tex]9.298 \\3.010-\\..........\\6.288[/tex]
Oriana was not correct, because she didn't line up the decimal points. Her procedure was:
[tex]9.298 \\ 0\ 3.01-\\..........\\8.997[/tex]
cos12sin78+cos78sin12
Sin 12 x cos 78 + cos 12 x sin 78
= sin 12 x cos (90-12) + cos 12 x sin (90-12)
=sin 12 x sin 12 + cos 12 x cos 12
=sin^2 12 + sin^2 12
=1
Please help me i really need it
Answer:
B and C
Step-by-step explanation:
It can't be A because that would equal 5b.
For C, you multiply 2b by 2 and get 4b.
For B, you add b to 3b to get 4b.
For which of the following statements is the inverse false? A. If a triangle is an equilateral triangle, then one angle equals 60°. B. If a triangle is a right triangle, then the other two angles add up to 90°. C. If a triangle is an equilateral triangle, then each of the angles equals 60°. D. If a triangle is a right triangle, then one angle equals 90°.
The statement for which the inverse is false is A, because if one angle of a triangle equals 60°, the triangle is not necessarily equilateral.
The question asks for which statement the inverse is false. To answer this, we analyze each statement and its inverse:
A. If a triangle is an equilateral triangle, then one angle equals 60°. Inverse: If one angle of a triangle equals 60°, then the triangle is equilateral. This could be false if the triangle is not equilateral but one angle happens to be 60°.
B. If a triangle is a right triangle, then the other two angles add up to 90°. Inverse: If two angles of a triangle add up to 90°, then it is a right triangle. This is true, given the geometric principle that the sum of angles in a triangle is 180°.
C. If a triangle is an equilateral triangle, then each of the angles equals 60°. Inverse: If each angle of a triangle equals 60°, then it is an equilateral triangle. This is true, as by definition, an equilateral triangle has all angles equal.
D. If a triangle is a right triangle, then one angle equals 90°. Inverse: If one angle of a triangle equals 90°, then it is a right triangle. This is true, as by definition, a right triangle has one 90° angle.
Therefore, the statement for which the inverse could be false is A.
Word expression to match 24-6+3
Answer:
I think itśn 5
Step-by-step explanation:
Solve the equation for Y 4x-10y = 12
4x - 10y = 12
4x - 12 = 10y
y = (4x - 12)/10
y = 2x/5 - 6/5
For f(x) = 3x +1 and g(x) = х2 - 6, find (f-g)(x).
Answer:
(f-g)(x) = -x^2 + 3x + 7
Step-by-step explanation:
Note that -g(x) = -x^2 + 6.
Thus, (f-g)(x) = f(x) + [-x^2 + 6]: Add the following:
f(x) = 3x + 1
-g(x) = -x^2 + 6
--------- ------------------
(f-g)(x) = -x^2 + 3x + 7 (answer)
In order for an atom to have a zero charge every proton which has a change of +1, must be matched with an electron which has a change of -1 a helium atom has 2 protons and 2 electrons explain why a helium atom has a zero change
A helium atom has a zero charge because the number of protons equals the number or protons. The positive and negative charges add together to reach zero.
Roselyn wants to drive her car at a speed of 606060 miles per hour for 1.251.251, point, 25 hours. Her car has a fuel efficiency of 151515 miles per gallon.
How many gallons of fuel does Roselyn need for her journey?
Answer:
Hence, there is 5 gallons of fuel Roselyn needed for her journey.
Step-by-step explanation:
Since we have given that
Speed at which Roselyn wants to drive her car = 60 miles per hour
Time taken by her car = 1.5 hours
As we know the formula for "Distance-Speed " :
Her car has fuel efficiency = 15 miles per gallon
Number of gallons of fuel is given by
Read more on Brainly.com - https://brainly.com/question/2059692#readmore
Answer:
5 gallons.
Step-by-step explanation:
Roselyn wants to drive her car at a speed of 60 mph
Speed of car, S = 60 mph
She drives for 1.25 hours.
Time travel, t = 1.25 hours
Total distance travel = s × t
= 60 × 1.25
= 75 miles
The fuel efficiency of car is 15 miles per gallon.
[tex]\text{Number of gallon used}=\dfrac{\text{Total distance travel}}{\text{Fuel efficiency}}[/tex]
[tex]\text{Number of gallon used}=\dfrac{75}{15}[/tex]
[tex]=5\text{ gallons}[/tex]
Hence, she needs 5 gallons.
x + 10 = 2x
PLEASE SHOW EXPLANATION + WORK
Answer:
X=10
Step-by-step explanation:
x+10-10=2x-10
x=2x-10
x-2x=2x-10-2x
-x= -10
-x/-1= -10/-1
x=10
evaluate 4 square root 9 square root 9 over 4 square root 9^5
[tex]\frac{\sqrt[4]{9}.\sqrt{9}}{\sqrt[4]{9^5}}[/tex]
[tex]\frac{9^\frac{1}{4}.9^\frac{1}{2}}{9^\frac{5}{4}}[/tex]
[tex]\frac{9^\frac{6}{8}}{9^\frac{5}{4}}[/tex]
[tex]9^{\frac{6}{8}-\frac{5}{4}}[/tex]
[tex]9^\frac{-1}{2}[/tex]
Which of the following polynomials is equivalent to the expression above?
A) x² + 5
B) x² +7
C) 4x² +7
D) x² + 4x + 7
Answer:
D) x² + 4x + 7
Step-by-step explanation:
2x + 6 + x² + 2x + 1
x² + 2x + 2x + 6 + 1
x² + 4x + 7
The equivalent expression for the given polynomial is x² + 4x + 7.
Option D is the correct answer.
What is a polynomial?Polynomial is an equation written as the sum of terms of the form kx^n.
where k and n are positive integers.
We have,
(2x + 6) + (x² + 2x + 1)
Removing the parenthesis.
2x + 6 + x² + 2x + 1
Adding the like terms.
4x + 7 + x²
x² + 4x + 7
Thus,
The final expression is x² + 4x + 7.
Learn more about polynomials here:
https://brainly.com/question/2284746
#SPJ2
The perimeter of a rectangle is 44 m. The length is 4 m more than the twice the
width. Find the dimensions.
Final answer:
The dimensions of the rectangle with a perimeter of 44 m, where the length is 4 m more than twice the width, are 6 m for the width and 16 m for the length.
Explanation:
The perimeter of a rectangle is given as 44 m, and the length (L) is said to be 4 m more than twice the width (W). To find the dimensions, we can set up the following equations based on the properties of a rectangle:
Perimeter P = 2(L + W)
L = 2W + 4
Since the perimeter is 44 m, we can substitute the length expression into the perimeter equation:
44 = 2((2W + 4) + W)
By solving this equation for width (W), we get:
44 = 2(3W + 4)
44 = 6W + 8
36 = 6W
W = 6 m
Now that we have the width, we can determine the length using the expression for L:
L = 2(6) + 4 = 16 m
Therefore, the final answer for the width is 6 m and the length is 16 m.
4 miles 999 feet = in feet
Answer:
approximately = 26394.72
Convert between the 2 units.
Can i plz have the brainliest answer plz!!!!!!!!!!!
2(2X-3)-10 <_ 6(X-2)
Answer:
x<14/5
Step-by-step explanation:
expand
4x-6-10 < -6x+12
4x-16 < -6x+12
4x < -6x+12+16
4x < -6x+28
4x+6x < 28
10x < 28
x < 28/10
hope this helps
Answer:
[tex]\large\boxed{x\geq-2\to x\in[-2,\ \infty)}[/tex]
Step-by-step explanation:
[tex]2(2x-3)-10\leq6(x-2)\qquad\text{use the distributive property}\ a(b+c)\\\\(2)(2x)+(2)(-3)-10\leq(6)(x)+(6)(-2)\\\\4x-6-10\leq6x-12\\\\4x-16\leq6x-12\qquad\text{add 16 to both sides}\\\\4x\leq6x+4\qquad\text{subtract}\ 6x\ \text{from both sides}\\\\-2x\leq4\qquad\text{change the signs}\\\\2x\geq-4\qquad\text{divide both sides by 2}\\\\x\geq-2[/tex]
Jenny’s Gift Shop sells candles in a variety of packages. The cost per candle is the same in every package. A package of 8 candles costs $12.96. Determine the cost of a package of 3 candles.
Answer:
8 candle = $12.96
1 candle =($12.96/8)
= $1.62
package of 3 candles =3×$(1.62)
: =$4.86
Find the slope of the line that passes through the points (-8,-3), (2,3)
Answer:
⅗
Step-by-step explanation:
-y₁ + y₂\-x₁ + x₂ = m
[tex] \frac{3 + 3}{8 + 2} = \frac{6}{10} = \frac{3}{5} [/tex]
I am joyous to assist you anytime.
Y/-7=10 solve and check
Always write y in lower case
y/-7 = 10
y = 10(-7)
y = -70
Check:
Let y = -70
(-70)/-7 = 10
10 = 10
Done!
The number 21 is decreased to 15. What is the percentage by which the number was decreased, to the nearest tenth of a percent?
Answer:
Initial Number = x = 21
Number after it is decreased = y = 15
Total decrease form initial to the current number = z = x-y = 21-15 = 6
% of decrease = (z/x) * 100 = (6/21)*100 = 600/21 = 28.5714286 = 28.6 ( correcting it to 10th place)
Step-by-step explanation:
For 21 decreased to 15, the percentage decrease is 28.6%.
The percentage by which a number was decreased can be calculated by finding the difference between the original number and the decreased number, dividing that by the original number, and then multiplying by 100 to get the percentage.
Given number: 21
On reduction, number becomes: 15
To find the percentage decrease:
(21-15)/21 x 100 = 28.6%.
Given the function below, select all the equalities that are true.
f(x) = x2 + 3
Answer:
a&c
Step-by-step explanation:
because you can multiply to numbers and reach 0 or 2, but no number times another equals 7 and no number times 0 equals three (multiplicative identity of 0)
Please help me with this
the answer is true it is a rational number
As a fraction, 2 is 2/1
Oh no, there is always an odd exponent. So it could not have been made by squaring a rational number! This means that the value that was squared to make 2 (ie the square root of 2) cannot be a rational number. In other words, the square root of 2 is irrational.
Select the correct answer.
Anton is approved for overtime at his job. Last week, he worked a total of 45 hours. How many hours of overtime did he work?
3 hours
B. 5 hours
C. 15 hours
D.45 hours
Answer: 15 hours
Step-by-step explanation: full time is 30 hours so if he worked 45 that’s 30+15=45 so 15hrs over time
6 x 7 - 3 + 2 = __
Insert parentheses to make the expression equal 26.
A) 6 x (7 - 3 + 2)
B) 6 x (7 - 3) + 2
C) (6 x 7 - 3) + 2
D) 6 x 7 - (3 + 2)
Answer:
B is the correct answer
Find the value of C. m^2+7/12m+c
Use b^2 - 4ac = 0.
Let a = 1
Let b = 7/12
(7/12)^2 - 4(1)c = 0
Take it from here.
If two is added to four times a certain number, the result
is 26. What is the number?
For this sort of question you have to work backwards.
.
26 - 2 = 24.
24 / 4 = 6
.
The number would be 6
This graph displays a linear function. What is the rate of change?
Answer:
rate of change is 5!!! :)
Step-by-step explanation:
Hope this helps!!! :)
The rate of change of the linear function in the graph is: 5
How to find the rate of change of the linear graph?Rate of change problems can generally be approached using the formula R = D/T, or rate of change equals the distance traveled divided by the time it takes to do so.
However, in this case with coordinates, it is expressed as:
Rate of change = (y₂ - y₁)/(x₂ - x₁)
From the graph, we can take two coordinates which are:
(1, -1) and (2, 4).
Thus:
Rate of change = (4 - (-1))/(2 - 1)
= 5/1
= 5
Read more about Linear Graph Rate of Change at: https://brainly.com/question/25184007
#SPJ3
solve problem y+7=-9
Answer: -16
Step-by-step explanation:
y + 7 = -9
-9 - 7 = -16
-16 + 7 = -9